(3LGeY GdMces - (3fUQ Hf eMeO Hf CMeO Hf EHQGgje GdnqSnerQnbrfOj, CHh GddjK, GdedbH HEeGe GdgOi,J (B373 (3g` s
(3ChdgG (B:s
(3bGd Gdabjg CHh GddjK QMeg Gddg Ef bGd dc bGjd eG GdMceI s
(3BNQgG (B:s
(3cd hGMO efgeG RjfI hRjfI GddMjI CcKQ dbhdg Ydjg GdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B91s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B540s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs